ASAS KEBIASAAN DALAM PENGGUNAAN GOOGLE PLAY BILLING SYSTEM BAGI PENGEMBANG APLIKASI DALAM DISTRIBUSI PRODUK DI GOOGLE PLAY STORE - Muyassar, Alifia Nada; Iwan Erer Joesoef (Fakultas Hukum Universitas Riau, 2025)
KPPU Decision Number 03/KPPU-I/2024 regarding the mandatory use of the Google Play Billing System (GPB) is an important milestone in the supervision of business competition in Indonesia's digital economy sector. Google is considered to have implemented an exclusive digital payment policy, forcing application developers to use GPB with a commission of 15-30% and limiting payment alternatives. This policy is considered to strengthen Google's dominant position in app distribution through the Google Play Store, which controls the majority of the market share. This study analyzes the KPPU's considerations in imposing a fine of IDR 202.5 billion and the application of legal principles, including the identification of abuse of dominant position and the evaluation of the impact of the policy on developers and consumers. Additionally, this study highlights the relevance of customary principles as stipulated in Articles 1339 and 1347 of the Civil Code in assessing the fairness of contractual terms between platforms and app developers. The results of the study show that the KPPU's decision emphasizes the importance of fair business competition, openness of payment systems, and protection of innovation in the digital ecosystem. The decision also sets a precedent for digital economy regulation and oversight of global platforms in Indonesia.